WEB-GIS FOR SCHOOL DATA MANAGEMENT AND ASSESSMENT IN KLATEN REGENCY - Rian Arif Hidayat; Ninik Agustin; Farly Detrias; Mochamad Taufiqurrochman Abdul Aziz Zein (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
Spatial presentation of data can provide broader information about an event or a feature that can facilitate drawing conclusions, for example using webGIS. WebGIS development in Klaten Regency has been implemented to display school data using licensed tools, but no development has been carried out using open source tools so that it is easy to customize. So, the development of a webGIS prototype is needed for the management and assessment of school data in Klaten Regency using open source tools. The system development methodology used is the waterfall model, with the phases of requirements analysis, design, implementation, and testing. The system was developed using the PHP language framework Code Igniter 4, MySQL database, front-end development in displaying maps using Leaflet.js and OpenStreetMap libraries. Spatial data of sub-district areas in the form of polygons is displayed using JSON and AJAX technology. School spatial data is displayed in the form of location point markers with school profile pop-ups. Functionality testing is carried out using the black box testing method resulting in all features functioning according to their functions.